The standardisation and streamlining of the process design - Pusula-Porre, Jenny Elina Erica (My University, 2023)
After outsourcing the process design several years ago, the knowhow of how to do process design decreased. The outsourcing is the reason why the level of process handbooks or oth-er information sources have been nonexistent. It has been the process designers’ responsi-bility to find or create the needed information, document, or program. Some of the company knowledge has only been knowhow in employees’ mind and official source for it has van-ished. The aim of this thesis was to gather all aspects that affect the producing of the process doc-umentation and create a handbook-wise approach to process design in Wärtsilä. The thesis starts with explaining process design phases and differences between the process documen-tation in these. The same chapter explains different project delivery types and classification principles. The next chapter introduces the standards that are affecting process documentation. The implementation of these standards and the biggest deviations in way of workings are located and presented. The physics behind the pressure drop calculations is introduced and the as-pects that affect the pressure drop are presented. After this, the needed programs and doc-uments are gathered into one chapter and a short explanation of these is given. In the end, the process document creation is explained step by step. Process documentation is a constantly developing branch in Wärtsilä. This is shaped according to standard’s, customer’s, and program’s requirements. The trend is that documents will contain more detailed information to the readers. There are several different directions where to take the process documentation development and the future challenge will be the creation of the most suitable version to the Wärtsilä projects.

Vuosia sitten tapahtuneen ulkoistuksen myötä prosessisuunnittelun tietotaito väheni Wärtsilässä merkittävästi. Tämän seurauksena, prosessisuunnittelua auttavia käsikirjoja tai muita kerättyjä tietolähteitä ei juurikaan ole ollut saatavilla. On ollut suunnittelijasta itsestä kiinni, kuinka on löytänyt suunnitteluun tarvittavat tiedot. Paljon tietoa on ollut myös vain henkilöiden omissa käsissä, eikä virrallista lähdettä tuolle tiedolle ole välttämättä ollut tiedossa. Tämän työn tarkoituksena oli koota kaikki vaikuttavat tekijät prosessidokumentaation tuottamiseen Wärtsilässä ja siten muodostaa käsikirjan tapainen lähestyminen prosessisuunnittelun vaiheisiin. Työ alkaa prosessisuunnittelun eri vaiheiden esittelyllä ja näiden vaiheiden eroavaisuuksissa dokumentaatiossa. Sama luku käsittelee myös eri projektien toimitustyypit ja näiden luokittelun. Seuraavassa luvussa nostetaan esille standardit, jotka vaikuttavat prosessisuunnittelun tuottamiin dokumentteihin. Standardien käyttö sekä suurimmat eroavaisuudet Wärtsilän työtavoissa paikannetaan ja esitellään. Laskutoimitusten takana oleva fysiikka kuvataan omassa luvussaan, käymällä läpi putkessa tapahtuvan painehäviön laskukaava ja siihen vaikuttavat tekijät. Seuraavaksi suunnittelussa tarpeelliset ohjelmat ja dokumentit kerätään yhteen, minkä jälkeen dokumentaation luomisprosessi käydään kohta kohdalta läpi. Prosessi dokumentaatio on alati kehittyvä osa-alue Wärtsilässä, jota muokkaavat niin asiakkaiden, standardien kuin ohjelmien vaatimukset. Tavoitteena on se, että dokumenteista tulee informatiivisempia lukijoille. Kehityssuuntia on monia ja tulevaisuuden haasteena onkin valita sopivin suunta Wärtsilän tuottamalle projektikohtaiselle dokumentaatiolle.
Keywords: standardit; prosessit; suunnittelu; projektit; fi=Energiatekniikka|en=Energy Technology|; fi=Energia- ja informaatiotekniikan ohjelma|en=Degree Programme in Energy Technology and Information Technology|